Necesidad de reformar el art. 558 del Código Orgánico Integral Penal, incorporando un inciso sobre la sanción a la persona que haga mal uso de las medidas de protección - Carvajal Montesdeoca, Flavio Enrique (2025)
This research analyzes the need to reform the Article 558 of the Integral Organic Penal Code by incorporating a provision regarding the sanction of individuals that misuse protective measures in order to protect those who are affected by the improper use or abuse of protective measures issued bunder this legal framework, or under the application of the Organic Integral Law for the Prevention and Eradication of gender-based violence against women, under which immediate administrative protective measures can be imposed based solely on the statement of the alleged victim or any other person. The research was carried out with a qualitative approach, explanatory scope, and a documentary research type; additionally, a survey was applied to obtain empirical arguments to support the proposal. The main conclusion is that the imposition of immediate administrative measures of protection affects the right to defense, the right to evidence, and the presumption of innocence, and in relation to these one such as the ones that were imposed under the COIP, frequently, the alleged victims misuse these protective measures as indicated b the survey results. As a proposal, the reform to the Article 558 of the COIP is suggested to include a provision that establishes sanctions of individuals who misuse protective measures.